Endoscopic management of primary obstructive megaureter in pediatrics. Issue 5 (October 2018) - Teklali, Youssef; Robert, Yohann; Boillot, Bernard; Overs, Camille; Piolat, Christian; Rabattu, Pierre Yves
Summary: Aims: The aims of this study were to evaluate the efficacy and safety of endoscopic treatment of primary obstructive megaureter in children, and to assess its long-term outcome. Methods: Case files of 35 children who had endoscopic treatment of symptomatic primary obstructive megaureter between 2006 and 2016 were retrospectively analyzed. All children had ureterovesical junction dilatation with one or more ureteral dilators, and insertion of a JJ stent. An analysis of the case files and a comparison between pre- and postoperative ultrasound and scintigraphy findings were performed. Results: The study population consisted of 22 boys and 13 girls aged between 2 months and 16 years. The follow-up period ranged from 8 months to 10 years. Twenty-one children (60%) were under 2 years at the time of treatment. The average duration of JJ stenting was 7 weeks (3–16 weeks). Thirty-four of 35 children (97%) were considered definitively cured, that is, asymptomatic with preserved renal function. Two children required open surgery for a failed endoscopic treatment procedure. Secondary reimplantation surgery was only necessary in one case (1/35) after technically satisfactory endoscopic treatment. Twelve of 35 children had a complication, including two Clavien III complications. Comparison of pre- and postoperative ultrasonography showed a significant decrease in ureteral diameter in 31 cases. Postoperative scintigraphy showed a significant improvement in the ureteral leaking curve in 20 children. Conclusion: In our experience, endoscopic treatment of congenital obstructive megaureter in pediatrics seems to be safe and effective. It is proposed as a first-line treatment for children requiring an intervention, even for young children under 2 years.